“I Did, I Did Taw a Puddy Tat!” Pumas in Urban Ecosystems of Latin America: A Review of the Mediatic Information - Guerisoli, María de las Mercedes; Schiaffini, Mauro Ignacio (Frontiers in Conservation Science, 2022)
The concentration of people living in small areas has increased in the last decade, with more than half of the world's population living in cities. This is particularly true for Latin America, a region with no particular high contribution to the world total population, but hosts several large cities. The increase in urbanization causes several threats to wildlife that face the loss of their habitat and novel environmental pressures. As the number of wildlife entering cities seems to have increased in the last year, we characterize the temporal and geographical events of a widely distributed carnivore, the puma, Puma concolor. We performed an exhaustive search for media news regarding the sighting, capture, and/or killing of pumas within human settlement areas, and tried to relate them with potential explanatory variables. We found a total of 162 events in Latin America in a period of the last 10 years, particularly concentrated in the year 2020. Most records came from Brazil, followed by Argentina, Chile, and Mexico. Of the total, 41% were only sightings, 58% were captures, and a minor percentage were considered as mascotism. Almost the same number of records came from highly populated areas (cities) than from low populated areas (rural) but with important differences between countries. The countries with more records in urban areas (Brazil and Mexico) showed a larger surface occupied by cities. The countries with most records in rural areas (Argentina and Chile) present the opposite pattern of occupied surface. This might indicate that different percentages of areas dedicated to cities or urban spaces might explain the differences among countries. The most important variable related to puma events in the populated areas was sky brightness, while human density and cattle density explained minor parts. The “anthropause” due to the COVID-19 pandemic might explain the larger number of records from 2020, while the absence of high-quality habitats due to fragmentation and high cattle density, might force the pumas to enter populated areas searching for food. Minor values of night lights could be related to a facilitation of efficiency of foraging behavior. Although some bias might exist in the data, the results should be taken into account as general statements for all analyzed countries.